Immunogenicity of the CYD tetravalent dengue vaccine using an accelerated schedule: randomised phase II study in US adults - Judith Kirstein; William Douglas; Manoj Thakur; Mark Boaz; Thomas Papa; Anna Skipetrova; Eric Plennevaux (BMC Infectious Diseases, 2018)
Abstract Background The live attenuated tetravalent dengue vaccine (CYD-TDV) is licensed using a 0-, 6- and 12-month schedule in dengue-endemic areas. An effective shorter schedule may provide more rapid, optimal protection of targeted populations during vaccine campaigns in dengue-endemic countries. We compared immune responses to two schedules of CYD-TDV in a non-endemic population. We also evaluated the impact of yellow fever (YF) co-administration. Methods This phase II, open-label, multicentre study enrolled 390 healthy 18–45-year-olds in the USA with no prior exposure to dengue. Participants were randomised (4:4:4:1) to four treatment groups stratified by prior YF vaccine status: Group 1, CYD-TDV standard 0–6–12 months schedule; Group 2, CYD-TDV accelerated 0–2–6 months schedule; Group 3, CYD-TDV accelerated schedule with YF co-administered (dose 1); Group 4, YF vaccination only. Neutralising antibody geometric mean titres (GMTs) and percentages of seropositive participants (antibody titres ≥10 [1/dil]) were measured against each dengue serotype using a 50% plaque reduction neutralisation test. Results On D28 post-CYD-TDV dose 3, there were no marked differences in seropositivity rates and GMTs between Groups 1 and 2. In Groups 1 and 2 respectively, 73.4 and 82.4% were dengue seropositive for ≥3 serotypes, with 50.0 and 42.6% seropositive against all four serotypes. Flavivirus status (FV+ or FV−) at baseline did not markedly affect GMTs and seropositivity rates with either schedule. In Groups 1 and 2, GMTs measured 6 months after the third dose decreased against all serotypes, except for a small increase in GMT for serotype 4 in Group 1. In addition, dengue seropositivity remained above 70% for serotypes 2, 3 and 4 in Groups 1 and 2. Co-administration with YF did not affect antibody responses against dengue and YF or impact vaccine safety following completion of the compressed schedule, compared to dengue or YF vaccination alone. Conclusions The live attenuated CYD-TDV vaccine given in a compressed schedule in a non-endemic setting can elicit similar antibody responses to the licensed CYD-TDV schedule. Trial registration This trial was registered on cinicaltrials.gov, NCT01488890 (December 8, 2011).